The collective actions in Catatumbo as a means for occupational reconfiguration of the agricultural sector - Vargas Prieto, Amanda; Figueroa Córdoba, Diana Paola (Cooperativismo & Desarrollo, 2020)
The armed conflict in Colombia has generated economic and social consequences that affect the understanding of local and regional development, bringing with them problems of land control in territories that have geostrategic advantages; such is the case of Catatumbo. Armed groups have entrenched themselves within this region, generating cultural rupture and limiting the occupational projects and hopes of its residents. This has resulted in a Territorial Vulnerability Index that reveals high rates of unemployment, violations of human rights and restrictions on processes of social participation. For this reason, this chapter analyzes the forms of collective resistance and their relationship with the changes in the productive and occupational practices of campesinos1 in the Catatumbo region. For this, it is important to analyze what is understood by collective action, occupational forms and the occupational expectations of a group of farmers, under a methodological framework of action research with three techniques of information collection: interviews, observation and workshops. The results made it possible to identify associativity, daily solidarity and strategic alliances as forms of resistance in the territory; collective actions that have determined the roles, personal history and occupational projections of its inhabitants based on individual and collective understandings, helping to reconfigure the territory and their occupations in search of alternatives for territorial development.
Keywords: collective action; occupational reconfiguration; territoriality; territorialization; territorial development